EFFECT OF ORGANIC MANURES AND NATURAL GROWTH STIMULANTS ON THE GROWTH AND QUALITY CHARACTERS OF BHENDI - M. ASHOK KUMAR; C. MALARVIZHI; K. DHANASEKARAN (The Bioscan, 2020)
Ten treatments were replicated thrice using randomized block design. The treatments details are T 1 - control (no treatment), T 2 - 100% recommended dose of NPK, T 3 - FYM @ 40 t ha -1 , T 4 - pressmud@ 40 t ha -1 , T 5 - FYM @ 40 t ha -1 + foliar application of panchagavya (3%), T 6 - FYM @ 40 t ha -1 + foliar application of vermiwash (10%), T 7 - FYM @ 40 t ha -1 + foliar application of humic acid (0.3%), T 8 - pressmud@ 40 t ha -1 + foliar application of panchagavya (3%), T9- pressmud@ 40 t ha -1 + foliar application of vermiwash (10%) and T 10 - pressmud@ 40 t ha - 1 + foliar application of humic acid (0.3%). Soil application of pressmud @ 40 t ha -1 along with foliar application of humic acid (T 10 -), recorded significantly highest value in both growth and quality characters like plant height (116.3 cm), number of leaves plant -1 (32.6), number of branches plant -1 (6.0), stem grith (3.72), leaf area index (6.92) and chlorophyll content (3.10 mg g -1 ), relative water content (85.4 per cent), ascorbic acid (15.42 mg 100g - 1 ), crude protein (1.65 per cent), total soluble solids (5.23 brix percent), titrable acidity (0.15 per cent) and low fiber content (9.85 per cent). The results of the field experiment proved that the application of bulky organic manures (FYM and Pressmud) at higher dose (40 t ha -1 ) significantly increased both the growth and quality characters. The untreated control (T1) treatment registered the least values.